al-‘Arabiyah Linnasyi'in: Analysis of Teaching Materials By Mahmud Ismail Shini, Nashif Musthofa Abdul 'Aziz, and Mukhtar Thahir Husain - Hidayatullah, Andri (Universitas Muhammadiyah Sumatera Barat, 2021)
Learning resources are an important aspect in the learning process, various models of arabic learning resources are raised by experts in accordance with the results of their research and development. In line with that the book